Current Trends in the Biosensors for Biological Warfare Agents Assay - Pohanka, Miroslav (Materials (Basel, Switzerland), 2019)
Biosensors are analytical devices combining a physical sensor with a part of biological origin providing sensitivity and selectivity toward analyte. Biological warfare agents are infectious microorganisms or toxins with the capability to harm or kill humans. They can be produced and spread by a military or misused by a terrorist group. For example, Bacillus anthracis, Francisella tularensis, Brucella sp., Yersinia pestis, staphylococcal enterotoxin B, botulinum toxin and orthopoxviruses are typical biological warfare agents. Biosensors for biological warfare agents serve as simple but reliable analytical tools for the both field and laboratory assay. There are examples of commercially available biosensors, but research and development of new types continue and their application in praxis can be expected in the future. This review summarizes the facts and role of biosensors in the biological warfare agents' assay, and shows current commercially available devices and trends in research of the news. Survey of actual literature is provided.
Keywords: biosensor; hand held assay; anthrax; tularemia; electrochemistry; biological weapon; colorimetry; bioassay; Bacillus anthracis; biological warfare agent; hemorrhagic fever